Assessing the association between the non-HDL to HDL cholesterol ratio and NAFLD in Chinese adults: concentrate on gout populations - Sun, Cunwei; Si, Ke; Zhu, Youzhuang; Li, Chengqian; Yu, Yang; Jia, Changxin; Wang, Qing (Frontiers in Nutrition, 2025)
BackgroundThe coexistence and synergistic relationship between Nonalcoholic fatty liver disease (NAFLD) and gout necessitate an investigation into the risk factors for NAFLD among individuals with gout. The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) serves as a comprehensive lipid index. This study aimed to investigate the association between NHHR and the risk of NAFLD in patients with gout.MethodsA cross-sectional study was conducted involving 1,038 hospitalized patients with gout to examine the relationship between NHHR and NAFLD. NHHR was included in the logistic regression analysis as both a continuous and a categorical variable. Restricted cubic splines (RCS) were utilized to assess the dose–response relationship. Additionally, subgroup analyses were performed to identify potential interactions among variables. The predictive capability of NHHR was evaluated using the receiver operating characteristic (ROC) curve based on the basic model.ResultsThe analysis of quartile groups stratified by NHHR levels revealed an increased prevalence of NAFLD corresponding to higher NHHR levels. Multifactorial logistic regression analysis established a significant association between NHHR and NAFLD, yielding an odds ratio (OR) of 1.242 [95% confidence interval (CI): 1.089–1.416, p = 0.001]. When treated as a categorical variable, the OR for NHHR in the fourth quartile was significantly elevated compared to the lowest quartile, with values of 1.993 (95% CI: 1.349–2.944, p = 0.001). The RCS analysis demonstrated a non-linear dose–response relationship between NHHR and NAFLD across all models. No significant interactions were detected in the subgroup analysis. Incorporating NHHR into the basic model enhanced the area under the curve (AUC) of the ROC curve to 0.706.ConclusionThis study identified a positive correlation between NHHR and the incidence of NAFLD in individuals with gout, suggesting that NHHR may serve as a reliable indicator of NAFLD within the gout patient.